509 - Influence of Self-perceptions of aging and attitudes towards aging on perceived health status. (October 2021) - Buedo-Guirado, Cristina; Dumitrache, Cristina G.; Rubio, Laura
Abstract: Objectives: Perceived health status is an important health indicator related to successfulaging and older people's quality of life. Perceived health status depends on biological, social and psychological factors, for example, at a social level, depends on comparisons with the peer group that individuals carry out and on attitudes towards aging, ageism andhow older people believe they are viewed by society. The aim of this study was to exploreattitudes towards aging and self-perceptions of aging among Spanish middle age and older people and to identify the influence on perceived health status. Method: The sample comprised 1, 124 individuals with ages between 50 to 98 years-old (M= 64.84, SD= 10.12) from the Aging in Spain Longitudinal Study database, Pilot Survey (ELES-PS). Results: Almost 70 per cent of the participants stated that old age begins at a specific chronological age and half of them considered that society treats older people with indifference. Self-perceptions of aging and attitudes towards aging were significant predictors that explain a 12.2% in the variance of perceived health status. Discussion: Results from this study highlight the importance of perceptions and attitudestowards aging for older adults' health. Addressing negative self-perceptions of aging andnegative attitudes towards aging can be particularly useful because they are associated with more pessimistic expectancies about the aging process.